(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper studied the mechanical properties of carbon fiber reinforced polybutylene terephthalate (PBT) composites, selected the different sizing agent to improve the interface binding capacity of carbon fibers (CFs) and PBT. Some CFs were modified with polyvinyl acetate (PVAc), and they were named p-C. Some other CFs were modified by ethylene acrylic acid (EAA), and they were named e-C. After modification, the groups of carboxyl were introduced into the surface of p-C. For e-C, the groups of C=C were introduced. For PBT/p-C composites, the maximum of tensile strength reached 68.22 MPa and elastic modulus reached 3263.18MPa, while the content of CFs is 15 wt.%. For PBT/e-C composites, with addition of the same content of CFs, the tensile strength and elastic modulus could reach 90.76 MPa and 4334.76 MPa respectively. Compared with pure PBT, the mechanical properties of the composites were improved significantly, and the reinforcement effect was more obvious in PBT/e-C composites, because of the better binding capacity between CFs and PBT. The decomposition temperature of the composites was between 378 ◦C and 417 ◦C, and they presented better heat resistance property.